2019
DOI: 10.3390/agronomy9040184
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Soil Chemical Properties and Mineral Nutrition in Relation to Growth and Yield Decline of Sesame on Different Continuously Cropped Upland Fields Converted Paddy

Abstract: Sesame (Sesamum indicum L.) is an important oilseed crop, but is negatively affected by continuous cropping. There is still a lack of information on the effect of continuous cropping on soil chemical properties and mineral nutrition related to sesame growth and yield decline. Therefore, we investigated sesame growth and yield, nutrient concentration and soil chemical properties on five fields with continuous cropping history: non-continuous cropping (Year 0) and durations of two, four, five and six years on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…The decrease in 1000-seed weight signifies that yield decline is consistent with Kelly et al [21], who found that yield decline of soybean under continuous monocropping is attributed to low seed weight. The decrease in 1000-seed weight and, consequently, yield of sesame has previously been attributed to decrease in N availability and to decrease in the uptake of K [7]. Our study showed markedly lower TN and exchangeable K in all continuously monocropped fields in 2016 when compared with those in 2015.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The decrease in 1000-seed weight signifies that yield decline is consistent with Kelly et al [21], who found that yield decline of soybean under continuous monocropping is attributed to low seed weight. The decrease in 1000-seed weight and, consequently, yield of sesame has previously been attributed to decrease in N availability and to decrease in the uptake of K [7]. Our study showed markedly lower TN and exchangeable K in all continuously monocropped fields in 2016 when compared with those in 2015.…”
Section: Discussionsupporting
confidence: 56%
“…Despite the importance of sesame seeds, the production of sesame in Japan had been on a negligible scale although it is gradually increasing, especially on abandoned paddy fields [5,6]. However, we previously reported yield decline of sesame on upland fields converted from paddy fields under intensive continuous monocropping as a result of changes in soil nutrient availability [7]. We reported decrease in available N and unbalanced exchangeable cations in which high quantities of Ca and Mg affected uptake of K. These changes or imbalances in soil nutrient status under continuous monocropping of sesame could affect sesame seed composition.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is reported that the growth and yield of crops decreased in long-term continuous monocropping due to several factors such as diseases, pests, depletion in soil nutrients, and nutrient imbalances [18]. Our previous study indicated that imbalances in soil exchangeable cations Ca, Mg, and K led to poor K nutrition as a result of high Ca and Mg inhibiting the uptake of K by sesame plants which partly limited sesame growth and yield under continuous monocropping on the upland field converted paddy [9]. Therefore, the poor growth of sesame in the un-balanced soil (control) confirmed the occurrence of continuous monocropping obstacle due to a low uptake of K. Apart from imbalances in cations Ca, Mg, and K, the decrease in K availability from continuous monocropping fields could be attributed to the annual removal of crop because sesame requires a high amount of potassium for growth and the seed usually accumulates a high amount of K as part of the mineral nutrient [8].…”
Section: Discussionmentioning
confidence: 99%
“…Sesame requires high concentration of K in the tissue, between 1.5% to 2.4%, and low K in the soil can cause poor growth [8]. However, our previous study reported that sesame growth is limited by poor K nutrition as a result of an imbalance in soil exchangeable cations that cause a competitive ion effect on continuous monocropping from upland fields converted paddy in Japan [9]. The decrease in the leaf tissue K content, and consequently its uptake, was attributed to an increase in soil exchangeable Ca and Mg in the long duration of continuous monocropping for four to six years, which caused a competitive ionic effect in the soil, thus negatively influencing the growth and yield.…”
Section: Introductionmentioning
confidence: 98%